Regulators of tubulin polyglutamylation control nuclear shape and cilium disassembly by balancing microtubule and actin assembly - Wang, Lei; Paudyal, Sharad C.; Kang, Yuchen; Owa, Mikito; Liang, Feng-Xia; Spektor, Alexander; Knaut, Holger; Sánchez, Irma; Dynlacht, Brian D. (Cell research, 2022)
Cytoskeletal networks play an important role in regulating nuclear morphology and ciliogenesis. However, the role of microtubule (MT) post-translational modifications in nuclear shape regulation and cilium disassembly has not been explored. Here we identified a novel regulator of the tubulin polyglutamylase complex (TPGC), C11ORF49/CSTPP1, that regulates cytoskeletal organization, nuclear shape, and cilium disassembly. Mechanistically, loss of C11ORF49/CSTPP1 impacts the assembly and stability of the TPGC, which modulates long-chain polyglutamylation levels on microtubules (MTs) and thereby balances the binding of MT-associated proteins and actin nucleators. As a result, loss of TPGC leads to aberrant, enhanced assembly of MTs that penetrate the nucleus, which in turn leads to defects in nuclear shape, and disorganization of cytoplasmic actin that disrupts the YAP/TAZ pathway and cilium disassembly. Further, we showed that C11ORF49/CSTPP1-TPGC plays mechanistically distinct roles in the regulation of nuclear shape and cilium disassembly. Remarkably, disruption of C11ORF49/CSTPP1-TPGC also leads to developmental defects in vivo. Our findings point to an unanticipated nexus that links tubulin polyglutamylation with nuclear shape and ciliogenesis.